CAML Does Not Modulate Tetherin-Mediated Restriction of HIV-1 Particle Release - Ali, Mohammed S. (Public Library of Science, 2010)
BACKGROUND: Tetherin/BST-2 is a recently-identified potent restriction factor in human cells that restricts HIV particle release following particle formation and budding at the plasma membrane. Vpu counteracts tetherin's restriction of particle release in a manner that has not yet been fully defined. We recently identified calcium-modulating cyclophilin ligand (CAML) as a Vpu-interacting protein that also restricts particle release. We hypothesized that CAML may act to enhance tetherin-mediated restriction of particle release and thereby explain how two distinct factors could be responsible for Vpu-responsive restriction. METHODOLOGY/PRINCIPAL FINDINGS: Endogenous levels of tetherin in human cells correlated well with their restriction pattern and responsiveness to Vpu, while levels of cellular CAML protein did not. Tetherin but not CAML was inducible by interferon in a wide variety of human cells. Stable depletion of human CAML in restrictive HeLa cells had no effect on cell surface levels of tetherin, and failed to relieve tetherin-mediated restriction. Stable depletion of tetherin from HeLa cells, in contrast, rendered HeLa cells permissive and Vpu-unresponsive. Tetherin but not CAML expression in permissive human cells rendered them restrictive and Vpu responsive. Depletion of CAML had no influence on cell surface levels of tetherin. CONCLUSIONS/SIGNIFICANCE: We conclude that tetherin restricts particle release and does not require CAML for this effect. Furthermore, these results do not support a major role for CAML in restricting HIV particle release in human cells.